Correlação entre a necessidade de tratamento, índice de absenteísmo odontológico e fatores socioeconômicos em escolares de uma Unidade de Saúde da Família: Guarulhos/ SP nos anos de 2016 e 2019 - Matos, Leonardo Paroche de (2020)
INTRODUCTION: caries has a high prevalence among schoolchildren and has the potential to cause sequelae, just as absences from consultations at services are notable and bring financial losses to management, cause loss of treatment opportunities and aggravate the repressed demand. OBJECTIVE: to describe the need for treatment and dental absenteeism in schoolchildren and correlate them with socioeconomic factors. METHODOLOGY: ecological, longitudinal retrospective study with a descriptive approach carried out in a Basic Health Unit that used data on risk classifications (P0, P1 and P2) obtained through an epidemiological survey in schoolchildren aged 0 to 12 years conducted in 2016 and 2019 for the description of the need for treatment and dental absenteeism index. The P0 risk classification and the absenteeism index were used for correlations with socioeconomic indicators. RESULTS: the Basic Health Unit presented averages of the need for treatment 2016: 22%, 2019: 28% and absenteeism 2016: 84%, 2019: 79%. Correlations: need for treatment P0: 2016- significant and positive: race/ black color, complete high school; significant and negative: walking; not significant and negative: not working and without health insurance. 2019- significant and positive: complete high school, without health insurance; not significant and positive: race/ black color; significant and negative: not working; not significant and negative: walking. Absenteeism: 2016- significant and negative: race/ black color, complete high school, walking, without health insurance; not significant and negative: not working. 2019- significant and negative: race/ black color, complete high school, without health insurance; not significant and negative: walking and not working. CONCLUSION: there was an average increase of 6% in the need for treatment and an average reduction of 5% in absenteeism in 2019; the correlations between the indicators and the need for treatment (P0 risk classification) showed varying patterns of distribution in the years of the study, in addition to all the negative correlations between socioeconomic indicators and absenteeism in 2016 and 2019.